Asia-Pacific: towards a new strategic balance? - Mindreau M., Manuel (1997)
Asia-Pacific is one of the world's arenas of major international competition and collaboration in the post-Cold War era. Over the past century and a half, the region has experienced recurrent great power rivalries, military intervention, colonialism, revolutions, and interstate as well as civil conflict. In recent decades, however, rapid and sustained economic growth has enabled the region to achieve unparalleled well-being, while enhancing the military power of numerous states. As the next century approaches, the crucial question is whether states in the Asia-Pacific will be able to create a political and security structure commensurate with their economic success. The absence of serious regional military crisis since the Sino-Vietnamese border war of 1979, and the emergence of region-wide economic institutions suggest such a prospect. However, the signs of stability may be misleading. Beneath a veneer of shared interests loom deeper differences and potential conflicts. Within this context, the continued military preference of the United States could tum into a geopolitical balancing factor for the stability of the entire region.